An Investigation of Depression, Trauma History, and Symptom Severity in Individuals Enrolled in a Treatment Trial for Chronic PTSD. Issue 7 (20th April 2015) - Bedard‐Gilligan, Michele; Duax Jakob, Jeanne M.; Doane, Lisa Stines; Jaeger, Jeff; Eftekhari, Afsoon; Feeny, Norah; Zoellner, Lori A.
<x xml:space="preserve">Abstract</x> Objective To explore how factors such as major depressive disorder (MDD) and trauma history, including the presence of childhood abuse, influence diverse clinical outcomes such as severity and functioning in a sample with posttraumatic stress disorder (PTSD). Method In this study, 200 men and women seeking treatment for chronic PTSD in a clinical trial were assessed for trauma history and MDD and compared on symptom severity, psychosocial functioning, dissociation, treatment history, and extent of diagnostic co‐occurrence. Results Overall, childhood abuse did not consistently predict clinical severity. However, co‐occurring MDD, and to a lesser extent a high level of trauma exposure, did predict greater severity, worse functioning, greater dissociation, more extensive treatment history, and additional co‐occurring disorders. Conclusion These findings suggest that presence of co‐occurring depression may be a more critical marker of severity and impairment than history of childhood abuse or repeated trauma exposure. Furthermore, they emphasize the importance of assessing MDD and its effect on treatment seeking and treatment response for those with PTSD.